A GALLUP SURVEY OF GEOGRAPHIC KNOWLEDGE IN THE SOVIET UNION. (Author: Gallup Organization) - Maconochie, A.K. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1991)
Gallup Organization. A GALLUP SURVEY OF GEOGRAPHIC KNOWLEDGE IN THE SOVIET UNION. Princeton, NJ. Gallup Organization, November, 1989. 53 pp.